Correlation Between cyclin G1 Expression and Efficacy of Radiotherapy on Primary Hepatocellular Carcinoma - XU Gang (Magazine House of Cancer Research on Prevention and Treatment, 2021)
Objective To investigate the correlation between cyclin G1 expression and the efficacy of radiotherapy on HCC. Methods The expression of cyclin G1 in biopsy specimens of 68 patients who received radiotherapy was detected by immunochemistry. The correlation between cyclin G1 expression and clinicopathological characteristics was analyzed by chi-square test. The correlation between cyclin G1 expression and OS or PFS was evaluated by Kaplan-Meier analysis. Univariate and multivariate analyses were used for the relation between clinicopathological characteristics and OS or PFS. Results The expression of cyclin G1 was related to portal vein tumor embolus, clinical stage and alpha fetoprotein. Survival analysis showed that the OS and PFS of patients with low expression of cyclin G1 were significantly higher than those with high cyclin G1 expression (P < 0.05). Multivariate analysis showed that cyclin G1 was an independent risk factor for DFS of patients with HCC. Conclusion High expression of cyclin G1 is an adverse prognostic factor for HCC patients who received radiotherapy.